IMPLEMENTASI PROGRAM DASHAT DENGAN PEMANFAATAN PANGAN LOKAL MELALUI KELOMPOK PRODUKSI BUMDES SEJAHTERA DESA KUNGKAI BARU KECAMATAN AIR PERIUKAN KABUPATEN SELUMA: IMPLEMENTASI PROGRAM DASHAT DENGAN PEMANFAATAN PANGAN LOKAL MELALUI KELOMPOK PRODUKSI BUMDES SEJAHTERA DESA KUNGKAI BARU KECAMATAN AIR PERIUKAN KABUPATEN SELUMA - yuliantini, emi (Poltekkes Kemenkes Bengkulu, 2025)
The Seluma Regency Government has formed a Cross-Sector Convergence Team for Reducing Stunting Rates which focuses on innovation and the use of local food. Local food available in local communities has not been fully utilized in programs to provide nutritional needs, especially to reduce the prevalence of stunting. Utilizing local food can be an important alternative to overcome food limitations and improve community nutrition. The aim of community service activities is to increase the knowledge of BUMDES Groups and Posyandu Cadres about health and local food utilization practices as well as quality early learning in the production of nutritious food with access to clean water and sanitation in Kungkai Village. Implementation of the DASHAT (Healthy Kitchens to Overcome Stunting) Program includes three models: social model, commercial model, and combination model. The Dashat program is an initiative launched to increase efficiency and productivity in local food management through technology and training. Intensive training for members of the BUMDES Sejahtera Production Group on more effective and efficient local food processing techniques. Through this Dashat program, it is hoped that Kungkai Baru Village can be more independent in managing its local food and optimize existing potential. With the support of new technology and knowledge, BUMDES Sejahtera is expected to be able to increase production capacity, expand markets and increase people's income. This program can be a useful model for other villages in Seluma Regency